DEVELOPMENT AND POTENTIAL OF SOYBEAN (Glycine max (L.) Merrill) IN BANJARNEGARA REGENCY - Khairi, Alfassabiq; Utari, Salwa Ramadina Putri; Zulfa, Faizatuz; Purnamasari, Ayu (Universitas Muhammadiyah Sidenreng Rappang, 2023)
Soybean (Glycine max (L.) Merrill) is a highly nutritious legume that is rich in protein, iron, and calcium. Soybeans are an excellent source of vegetable nutrition for the human body and contain nutrients such as carbohydrates (20–30%), lipids (19%), essential fatty acids, phosphorus, iron, calcium, zinc, thiamine, riboflavin, vitamin E (tocopherol), dietary fiber (16%), and sugar. The potential for developing agricultural products has the potential to increase, marked by increased consumer demand which is soybean that has the potential to be developed due to production development in Banjarnegara Regency increasing annually. The research aims to determine the potential for developing soybeans in Banjarnegara Regency through historical data on plant cultivation. This research was carried out in September–October 2023. The research method used was qualitative research. This research data is secondary data obtained through the Central Statistics Agency (BPS) website and the Food and Agriculture Organization Corporate Statistical Database (FAOSTAT). The data obtained were analyzed using Pearson’s correlation analysis and simple regression at the 95% level. Furthermore, data forecasting analysis (forecasting) was also carried out to determine soybean productivity in 2023. The data was analyzed and displayed in graphical form using the Minitab v.21.4 application, while the data was displayed in tabular form using Microsoft Excel 2019. The conclusion is the development of soybean plants in the Regency Banjarnegara can be stable and increase every year, this needs to be maintained through local government policies, agricultural services, and researchers at institutions/universities to maintain the stability of soybean production and food security in the present and future.